Seasonal variation in the abundance and distribution of Anomalocardia flexuosa (Mollusca, Bivalvia, Veneridae) in an estuarine intertidal plain - Silva-Cavalcanti, Jacqueline S.; Costa, Monica F.; Alves, Luis H.B. (PeerJ, 2018)
Spatial and temporal density and biomass of the infaunal mollusk Anomalocardia flexuosa (Linnaeus, 1767) evaluated a tidal plain at Goiana estuary (Northeast Brazil). Three hundred and sixty core samples were taken during an annual cycle from three intertidal habitats (A, B and C). Shell ranged from 2.20 to 28.48 mm (15.08 ± 4.08 mm). Recruitment occurred more intensely from January to March. Total (0–1,129 g m−2) differed seasons (rainy and dry), with highest values in the early rainy season (221.0 ± 231.44 g m−2); and lowest values in the late dry season (57.34 ± 97 g m−2). The lowest occurred during the late rainy (319 ± 259 ind m−2) and early dry (496 ± 607 ind m−2) seasons. Extreme environmental situations (e.g., river flow, salinity and water temperature) at the end of each season also affected density ranges (late dry: 0–5,798 ind m−2; late rainy: 0–1,170 ind m−2). A. flexuosa in the Goiana estuary presented a dominance of juvenile individuals (shell length < 20 mm), with high biomass main the recruitment period. Average shell length, density and biomass values suggest overfishing of the stock unit. A. flexuosa is an important food and income resource along its whole distribution range. The species was previously also known as Anomalocardia brasiliana (Gmelin, 1791).
Keywords: Traditional fisheries; Population dynamics; Size classes; Anomalocardia brasiliana; Estuarine ecology